A Study on γ - Optimization Parameter and Phase Margin of Fourth Order Phase-Locked Loop - Borah, Munmee; Bezboruah, Tulshi (International Journal of Computer Sciences and Engineering, 2018)
A 4th order phase-locked loop model by considering two different filter configurations in the loop have been developed and behavioral simulation has been performed on MATLAB platform to study the impact of gamma-optimization parameter on it and also to study the stability of the system in terms of phase margin. We have also investigated the bandwidth and lock time of the system.